2017
DOI: 10.1186/s12957-017-1269-2
|View full text |Cite
|
Sign up to set email alerts
|

An acetabular-preserving procedure for pelvic giant cell tumor involving partial acetabulum

Abstract: BackgroundThe management of pelvic giant cell tumors (GCTs) involving the acetabulum remains a challenge for surgeons on how to balance the relative benefits of minimizing recurrence and maintaining postoperative hip function. The present study was to present and evaluate the clinical indications, operative technique, and outcomes of pelvic GCTs involving partial acetabulum treated with multiplanar osteotomy and reconstruction of autogenous femoral head bone grafts combined with cementless total hip arthroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, our results and some relevant research showed that reconstruction with autologous femoral head grafting is feasible, and we still need more cases for verification. Although those classifications are great guides to the reconstruction of bone defects in THA revision, it does not seem to be widely used for the bone defects in periacetabular tumors resection [ 24 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results and some relevant research showed that reconstruction with autologous femoral head grafting is feasible, and we still need more cases for verification. Although those classifications are great guides to the reconstruction of bone defects in THA revision, it does not seem to be widely used for the bone defects in periacetabular tumors resection [ 24 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This surgical principle is to make a corner osteotomy around the bone tumor to achieve a limited and extensive resection, so as to maximize the preservation of normal bone and soft tissue around the tumor. Some studies had applied this principle in clinical practice and achieved satisfied prognosis [ 22 24 ]. Inspired by those studies, we considered whether the treatment of periacetabular bone tumors could follow the principle of multiplanar osteotomy, in order to retain the patient’s bone mass, especially the part of the acetabulum [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with a long disease history, the tumor is always massive, and wide margin resection to avoid recurrence along with reconstruction with a sufficient biomechanical stress load can be even more challenging because of the large bone defect. 11 13 …”
Section: Discussionmentioning
confidence: 99%
“…In patients with a long disease history, the tumor is always massive, and wide margin resection to avoid recurrence along with reconstruction with a sufficient biomechanical stress load can be even more challenging because of the large bone defect. [11][12][13] With the developments in tissue engineering material technology, medical imaging, and 3D imaging techniques, computer-aided design of 3D orthopedic surgical implants is being more frequently used by surgeons. 14,15 In the present case, we obtained the CT data from the PACS, used Mimics 17.0 software for reconstruction, and used a 3D printing system to print out the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty was carried out primarily in these cases. Xiao et al [ 12 ] described seven patients of giant cell tumor involving acetabulum. Partial excision of the acetabulum was carried out along with reconstruction using the autologous femoral head.…”
Section: Discussionmentioning
confidence: 99%